Safety Toxicology Study of Reassortant Mopeia–Lassa Vaccine in Guinea Pigs - Bradley S. Wahle; Peter Pushko; Katie Albanese; Dylan M. Johnson; Irina Tretyakova; Igor S. Lukashevich; Thomas Rudge (Future Pharmacology, 2025)
(1) Background: Mopeia–Lassa reassortant ML29 virus is an investigational, reassortant virus vaccine for the prevention of Lassa fever caused by Lassa virus (LASV). (2) Methods: The vaccine virus ML29-SF was prepared in Vero cells using a serum-free culture medium under Good Manufacturing Practice. A 2-week repeat dose toxicity study was performed in guinea pigs under Good Laboratory Practice (GLP) regulations to assess the local and systemic toxicological effects. (3) Results: Following an intramuscular (IM) or subcutaneous (SC) injection of 104 PFU of ML29-SF LASV vaccine at the start of the study, with a second dose 15 days later, no toxicological response attributable to the vaccine was observed. Vaccine-related effects were not observed in any in-life or post-mortem parameter evaluated, including clinical observations, injection site observations, body temperature, body weight, food consumption, ophthalmology, immunology, hematology, clinical chemistry, gross anatomical pathology, organ weights, and histopathology. An immunogenic response, as measured by the elicitation of IgG antibodies against major LASV immunogens, nucleocapsid and glycoprotein precursor, was observed in all vaccine-treated animals prior to the booster dose (Study Day 15) which endured through the end of the study (Study Day 42). There was no evidence of viral shedding in any vaccinated animal. (4) Conclusions: Overall, this single-dose vaccine was locally and systemically well tolerated even after a two-dose repeat administration, confirming the high level of safety of ML29-SF vaccination and supporting the future evaluation of this LASV vaccine, including in clinical trials.